2008
DOI: 10.1515/cclm.2008.277
|View full text |Cite
|
Sign up to set email alerts
|

Methionine metabolism in an animal model of sepsis

Abstract: Background: Sepsis is a disease with high incidence and lethality and is accompanied by profound metabolic disturbances. In mammalian methionine metabolism, S-adenosylmethionine (SAM) is produced, which is important in the synthesis of neurotransmitters and glutathione and as an anti-inflammatory agent. The degradation product and antagonist of SAM is S-adenosylhomocysteine (SAH). In this study, we investigated changes in methionine metabolism in a rodent model of sepsis. Methods: Sepsis was induced in male Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 35 publications
4
10
0
Order By: Relevance
“…High SAM levels have previously been observed after experimental lipopolysaccharide challenge in rats. 5 Finally, we found that elevated SAM and SAH levels in nonsurvivors versus survivors can be accounted for by more severe renal impairment in the nonsurvivors. The important effect of renal function is further supported by the observation that declining SAM and SAH levels over time are accompanied by declining creatinine concentrations (in survivors), and persistent elevations in SAM and SAH levels are accompanied by persistent renal dysfunction (in nonsurvivors; Table 5).…”
Section: Implications Of the Study Findingsmentioning
confidence: 66%
See 1 more Smart Citation
“…High SAM levels have previously been observed after experimental lipopolysaccharide challenge in rats. 5 Finally, we found that elevated SAM and SAH levels in nonsurvivors versus survivors can be accounted for by more severe renal impairment in the nonsurvivors. The important effect of renal function is further supported by the observation that declining SAM and SAH levels over time are accompanied by declining creatinine concentrations (in survivors), and persistent elevations in SAM and SAH levels are accompanied by persistent renal dysfunction (in nonsurvivors; Table 5).…”
Section: Implications Of the Study Findingsmentioning
confidence: 66%
“…Dysregulated methionine metabolism has been implicated in cardiovascular disease 3,4 and sepsis. [5][6][7][8] Methionine is enzymatically converted to S-adenosylmethionine (SAM), the major substrate for transmethylation reactions 9 and initial precursor for homocysteine and glutathione production (Figure 1). S-adenosylhomocysteine (SAH) is the by-product of SAM transmethylation reactions, is in equilibrium with homocysteine, and provides negative feedback regulation on methyltransferase activity.…”
Section: Introductionmentioning
confidence: 99%
“…These metabolites may offer a more relevant, amplified signature in sepsis and can be measured using techniques such as 1 H nuclear magnetic resonance (NMR) spectroscopy or mass spectrometry (MS) [9]. To date, the application of metabolomic (or metabonomic) profiling in sepsis is limited to animal studies [1013], or to specific metabolic pathways, such as tryptophan/kynurenine [14], arachidonic acid [15], or arginine metabolism [16], among others [17]. One study found using 1 H-NMR found differences in glutathione, adenosine, sphingomyelin, and phosphatidylserine between healthy controls and ventilated patients with sepsis-associated acute lung injury [18].…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] A major source of cysteine is transsulfuration from homocysteine (Hcy), a pathway which is also affected in sepsis. 11,12 A recent study focusing on the plasma metabolome in septic patients revealed correlation of alpha-n-aminobutyric acid with the patients Sequential Organ Failure Assessment (SOFA) Score and cystathionine levels. 13 Both cystathionine and alpha-n-aminobutyric acid are metabolites of Hcy downstream of the cystathionine betasynthase (CBS, EC 4.2.1.22) reaction.…”
Section: Introductionmentioning
confidence: 99%